The position of Az-Zamakhshari regarding the Quranic recitations in his interpretation of Al- - Matroud, Dr.Hussein Shaweil (Thi Qar Arts Journal, 2023)
This research deals with the interpretation of Al-Kashshaf and represents some of the readings that Al-Zamakhshari stopped at to show his position on them. Or he finds it from the opinion of the reader and his diligence, or he composes the reader, or attributes to him an illusion, then the research tries to stand on the reasons that made Al-Zamakhshari take this position, and the motives that led to his adoption of this position.